2022
DOI: 10.4995/wrs.2022.17160
|View full text |Cite
|
Sign up to set email alerts
|

Sample preparation and storage effects on fatty acid profile of rabbit Longissimus thoracis et lumborum muscle

Abstract: Twenty-five Pannon White male rabbits reared and fed in similar conditions were slaughtered at 11 weeks of age. The longissimus thoracis et lumborum muscles (LTL; right and left) were removed at 24 h post-mortem and allocated to four sampling/storage treatments: the left side of LTL muscle was divided in half perpendicularly, with the posterior portion being analysed within one day (fresh), and the anterior portion vacuum packaged and stored for 1 mo at –20°C (whole-frozen); the right LTL side was ground with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
1
1
0
Order By: Relevance
“…ARA can also be converted to the longer PUFA—DPA; this conversion ability was not demonstrated in this study in terms of the higher ARA content and lower DPA content recorded in the experimental groups. The n -6/ n -3 ratio corresponds to the values reported by Dalle Zotte et al [ 40 ], but it was found at a lower level (14.626–16.102), compared to the previous experiment with the inclusion of Ent M and sage in the diet, reaching values 22.26–24.33 for LTL [ 18 ]. However, we have only preliminary data regarding the effect of enterocins on the FA composition of rabbit meat, but these results suggest that Ent M can improve the biological value of rabbit meat.…”
Section: Discussionsupporting
confidence: 79%
“…ARA can also be converted to the longer PUFA—DPA; this conversion ability was not demonstrated in this study in terms of the higher ARA content and lower DPA content recorded in the experimental groups. The n -6/ n -3 ratio corresponds to the values reported by Dalle Zotte et al [ 40 ], but it was found at a lower level (14.626–16.102), compared to the previous experiment with the inclusion of Ent M and sage in the diet, reaching values 22.26–24.33 for LTL [ 18 ]. However, we have only preliminary data regarding the effect of enterocins on the FA composition of rabbit meat, but these results suggest that Ent M can improve the biological value of rabbit meat.…”
Section: Discussionsupporting
confidence: 79%
“…Rabbit meat quality is dictated by muscle fiber type and characteristics that arise during skeletal muscle development ( Du et al, 2022 ). The M. longissimus thoracis et lumborum is the largest erector spinae muscle and is commonly used for meat quality assessments in rabbits and other animals ( Zotte et al, 2022 ), thus providing an ideal model to study feed efficiency.…”
Section: Introductionmentioning
confidence: 99%